Eye of the Tiger Sign in Pantothenate Kinase-Associated Neurodegeneration - S. Choayb; H. Adil; Daoud Ali Mohamed; N. Allali; L. Chat; S. El Haddad (Case Reports in Radiology)
Pantothenate kinase-associated neurodegeneration (PKAN) is a rare disorder associated with brain iron accumulation caused by a recessive mutation in pantothenate kinase 2 gene (PANK2). We present a case of an 11 year-old boy presenting extrapyramidal signs and developmental regression. T2-weighted images showed the classic eye of the tiger sign seen in pantothenate kinase-associated neurodegeneration.